GERAKAN MURAL DAN PEMBUNGKAMAN KEBEBASAN BERPENDAPAT DIMASA PANDEMI TAHUN 2021 (STUDI KASUS LOMBA "DIBUNGKAM" GEJAYAM MEMANGGIL DI YOGYAKARTA) - Daud Yunus Susanto (2023)
The silencing of freedom opinion and expression through removal critical murals in several Indonesian cities occurred during COVID-19 pandemic. The shrinking of civic space was one of the factors. Murals criticizing the government's performance, the economic situation, health, and people's welfare during COVID-19 were removed by the government. The mural contains a message that the country is not doing well, due to corruption in social assistance and restrictions on space for public opinion and expression by the government. This repressive action by the government became the origin of Gejayan Calling in creating the "DIBUNGKAM" mural competition as a collective movement of the people to express their claims against the government. Focus of this research is to explain how the contentious politics movement through murals emerged after the repressive actions by removing murals in several cities in Indonesia, in the "DIBUGKAM" competition by Gejayan Calling in 2021. This research uses descriptive qualitative methods and this research approach uses a case study approach. The theory used is contentious politics by Charles Tilly and Sidney Tarrow, namely there are three general characteristics, namely enmity, collective action, and politics. The data collection techniques used in this study are primary and secondary data and use interactive data analysis techniques from Miles and Huberman, namely data condensation, data display, and conclusion/verification. The results of this study indicate that the narrowing of civil space does occur, the community's claims against the government that do not have access are assisted by the "SILENCED" Gejayang Calling competition as a collective action. The competition was attended by people from various cities in Indonesia. As well as displayed via Instagram Gejayan Calling. Claims that the government uses substantial means of coercion using the army, police, and community organizations that cooperate with the government, to carry out repressive actions ranging from hunting for muralists, removing murals criticizing participants, to making mural competitions as their political communication indicating that there is no anti-criticism in the body. the government especially the Police of the Republic of Indonesia.